MENTORING AND COACHING IN A WORKPLACE LITERACY PROGRAM - Mahendran, Siva (International Journal of Research -GRANTHAALAYAH, 2025)
This study explores the implementation of mentoring and coaching as strategic tools to enhance workplace English literacy in a post-pandemic context. As organizations increasingly prioritize reskilling and upskilling to maintain employability, this qualitative research examines how personalized support mechanisms—mentoring and coaching—address communication and emotional intelligence gaps among employees. Drawing on data from interviews, surveys, and workplace case studies, the study highlights how these approaches improve employee confidence, communication, engagement, and overall productivity. Mentoring fosters long-term developmental relationships for holistic growth, while coaching targets specific, measurable literacy outcomes. Successful implementation involves needs assessments, trained mentors/coaches, clear objectives, on-the-job integration, and ongoing evaluation. Despite challenges like time constraints and resource limitations, the findings affirm that mentoring and coaching significantly uplift workplace literacy, strengthening both individual career progression and organizational performance.